Cancellation of Wills in Civil Inheritance Law: Conditionsand Legal Effects - Noviya, Anis (Leges Privatae, 2024)
This study aims to analyze the conditions and legal consequences of the cancellation of wills in civil inheritance law. In inheritance law, a will is an instrument that gives the heirs the freedom to determine the division of wealth as they wish. However, the cancellation of a will often occurs due to changes in the condition or wishes of the heir before he dies. This study uses normative juridical methods, with an approach to laws and regulations and literature studies to examine juridical aspects related to the cancellation of wills, conditions that must be met, and legal implications for heirs. The results of the study show that the annulment of a valid will must meet certain formal requirements, such as being carried out by heirs who have legal capacity and are in good mental health. Cancellation that is not in accordance with the procedure can result in legal uncertainty and disputes among the heirs, as a will that was previously considered invalid can be considered valid again. The legal consequences of this annulment of a will include changes in the distribution of inherited property, which can be done under general inheritance law if there is no new valid will. This study highlights the importance of procedural clarity and legal education so that heirs and heirs understand the impact of the act of annulment.